Relationships between Visual Figure Discrimination, Verbal Abilities, and Gender. (September 2013) - Tammik, Valdar; Toomela, Aaro
This study investigated the relationships between verbal thinking and performance on visual figure discrimination tasks from a Vygotskian perspective in a large varied adult sample ( N = 428). A test designed to assess the structure of word meanings (ie tendency to think in 'everyday' or 'scientific' concepts as distinguished by Vygotsky) together with two contour picture tasks was presented. Visual tasks were a modified version of Poppelreuter's overlapping figures and a picture depicting a meaningful scene. On both tasks concrete objects and abstract meaningless shapes had to be identified. In addition to relationships between visual task performance and word meaning structure, the effects of the meaningful scene and relations with gender were examined. The results confirmed the expected relation between word meaning structure and visual performance. Furthermore, they suggested a specific effect of the meaningful whole and a male advantage, especially for the first task in which women seemed to benefit less from advanced word meaning structure.